The Influence of Competence, Work Discipline, and Teamwork on the Performance of Employees of PT Lion Mentari Airlines at I Gusti Ngurah Rai International Airport - Aril Amanda Putri; Dewi Andriani; Kumara Adji Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
Employee performance can be measured by their ability to complete all the work that is their responsibility. The decline in employee performance at Lion Air is characterized by a lack of knowledge of company procedures, high levels of tardiness and absenteeism, and a lack of communication and coordination between team members. This study seeks to examine the impact of competency, work discipline, and teamwork on the performance of employees at PT Lion Mentari Airlines. This study uses a quantitative method. The population of this study is the operational employees of Lion Air Ngurah Rai Airport, with a sampling technique using a total sample of 100 employees. The data source used is primary data obtained from distributing questionnaires via Google Forms. Data analysis was carried out using SmartPLS software version 4.0. This study's findings demonstrate that Competence, Work Discipline, and Teamwork positively and significantly influence employee performance.